Proceedings of 6th Eurasphalt &Amp; Eurobitume Congress 2016
DOI: 10.14311/ee.2016.082
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and recovery of polymer modified bitumen

Abstract: The amount of heavy traffic is increasing continuously asking for high performance road pavements. The higher requirements in terms of stability and fatigue behavior are the main reason for the elevated use of polymer-modified bitumen (PmB). Despite the fact that PmB have been known and used for several decades, standardization is still inadequate in some parts. Only in 2012, the standards for binder extraction and has been adapted to PmB. Still, binder results obtained by the extraction with different solvent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The main aspects cited in the literature on solvent extraction and binder recovery were: (i) application of different types of solvents and their effects on the characteristics of the asphalt binders ( 14 16 , 18 , 19 ); (ii) effect of the extraction methods on the binder content determination and on the physical, rheological, and chemical properties of conventional or modified binders ( 13 , 14 , 20 – 22 ); (iii) efficiency of solvent removal from asphalt binder samples by Abson and/or rotavapor procedures, in addition to the influence of both techniques on its physical, rheological and chemical characteristics ( 1 , 13 , 17 , 20 , 23 – 25 ). Despite the common points investigated, there are still divergences among authors over the variations in the intrinsic characteristics of asphalt binder after passing through different extraction and recovery techniques.…”
Section: Extraction and Recovery Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The main aspects cited in the literature on solvent extraction and binder recovery were: (i) application of different types of solvents and their effects on the characteristics of the asphalt binders ( 14 16 , 18 , 19 ); (ii) effect of the extraction methods on the binder content determination and on the physical, rheological, and chemical properties of conventional or modified binders ( 13 , 14 , 20 – 22 ); (iii) efficiency of solvent removal from asphalt binder samples by Abson and/or rotavapor procedures, in addition to the influence of both techniques on its physical, rheological and chemical characteristics ( 1 , 13 , 17 , 20 , 23 – 25 ). Despite the common points investigated, there are still divergences among authors over the variations in the intrinsic characteristics of asphalt binder after passing through different extraction and recovery techniques.…”
Section: Extraction and Recovery Techniquesmentioning
confidence: 99%
“…Studies seek to evaluate the effect of the aged RAP binder on the performance of recycled asphalt mixtures and to determine the binder blend properties, especially when high levels of RAP are incorporated into the new mixtures (9,11,12). Some authors have also investigated and reported the effects that different extraction methods, types of solvents, and recovery processes have on the recovered asphalt binder properties (1,4,(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%